Mudança de estilo de vida em situações de risco cardiovascular : um olhar do paciente - Gois, Rachel Barreto Sotero de Menezes (2014)
Introduction: Cardiovascular diseases remain the leading cause of morbidity and mortality worldwide. One of the most recommended interventions for cardiovascular risk reduction is lifestyle change, but which in practice presents low adherence. Despite the obstacles for adopting a healthy lifestyle, some subjects feel motivated and achieve this objective. Objective: Knowing motivations of a group of patients with cardiovascular risk factors in outpatient medical management adopted a healthy lifestyle from a cardiovascular point of view. Methodology: An exploratory and qualitative research, using information from the records of the subjects and semi-structured interview, conducted with patients in outpatient clinical care, in the city of Aracaju/SE, Brazil with a sample consisting of twelve participants. Patients with coronary heart disease or stroke who underwent bariatric surgery and users of drugs for body weight reduction were excluded. Thematic analysis was conducted on the speeches of the participants. Results and Discussion: Information from medical records yielded information tables with the subject´s profile and risk factor indicators. Answers to interviews were separated into two groups. The first was composed of themes related to the subject, from this originated seven categories, namely: conception about life, fear of loss and death, religious thought, influence of interpersonal relationships, preoccupation with genetics, gains and change. The second was composed of topics related to the relationship with the health professional, originated the category patient- doctor meeting. There was no discussion of the results based on the specialized literature. Conclusions: It is noticed that motivation for lifestyle change were overcome by intrinsic and extrinsic factors with the subjects. In the data collected, there was a predominance of internal motivations. The subjects demonstrated actions grounded in the reality of the information on health and cardiovascular risk that they presented. In a gradual process, they were becoming authors of their own decisions, capable of dealing with the consequences of the choices they made. The impulse for life was predominant so that changes were adopted and maintained. In relation to external motivations related to the importance of how doctors communicated, as well as the affectivity present in the doctor-patient relationship. This study may contribute to the reflection on the clinical care, suggesting an investment in the subjectivity of the patient in order to obtain better results for adherence to lifestyle change measures.